An analysis of the impact of democratization on debt-led growth : the Nigerian experience, 1970-2000 - Dinneya, Godson Eze (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
The debt-for democracy hypothesis is that undemocratic governments were largely responsible for not only the accumulation but also poor management of externally sourced capital resources. External borrowing had therefore failed to lead to growth of the economies of debtor countries under undemocratic political leadership. Despite this explanation of the debt problem conventional empirical analyses of the debt-growth relationship did not include political institutional variables. This study investigates the relationship between democratization and debt-led growth, using Nigeria, a typical debtor country whose politics was dominated by 'undemocratic ' governance, as a case study. Two broad research questions are investigated namely, whether available data support a negative or positive contribution of debt to the growth of the Nigeria economy during the period 1970-2000
Keywords: Debts, External -- Nigeria; Nigeria -- Politics and government -- 1960-; Nigeria -- Economic policy; Nigeria -- Economic conditions -- 1960-